2000
DOI: 10.1046/j.1365-2230.2000.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase digestion and mechanical disaggregation as a method to extract and immunophenotype tumour lymphocytes in cutaneous T-cell lymphomas

Abstract: Various enzymatic or mechanical methods have been proposed in the past to dissociate cells from different solid tissues. An automated mechanical disaggregation device (Medimachine) has recently been proposed. Unfortunately, most of these techniques are associated with a high cellular damage and a low cell recovery and are difficult to apply to skin biopsies. In this paper, we propose a combined enzymatic and mechanical method based on Medimachine, useful for the isolation of skin infiltrating T-lymphocytes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Interestingly, enzymatic digestion yielded 74%-76% viability irrespective of the tissue characteristics (i.e., fresh or cryopreserved, complete spermatogenesis or arrest), whereas tissue characteristics had a more pronounced effect on the viability after mechanical dissociation, which ranged from 38% in fresh tissues to 8% in cryopreserved tissues with a meiotic arrest. These findings are generally in accordance with a previous study reporting that mechanical dissociation resulted in a higher number of dead cells compared with an alternative dissociation procedure of cutaneous T-cell lymohomas (29). However, our results are in contrast to a study that used testicular tissue from rodents, including mice, rats, and guinea pigs, and found a viability of >85%.…”
Section: Figuresupporting
confidence: 92%
“…Interestingly, enzymatic digestion yielded 74%-76% viability irrespective of the tissue characteristics (i.e., fresh or cryopreserved, complete spermatogenesis or arrest), whereas tissue characteristics had a more pronounced effect on the viability after mechanical dissociation, which ranged from 38% in fresh tissues to 8% in cryopreserved tissues with a meiotic arrest. These findings are generally in accordance with a previous study reporting that mechanical dissociation resulted in a higher number of dead cells compared with an alternative dissociation procedure of cutaneous T-cell lymohomas (29). However, our results are in contrast to a study that used testicular tissue from rodents, including mice, rats, and guinea pigs, and found a viability of >85%.…”
Section: Figuresupporting
confidence: 92%
“…The potential of FC as a diagnostic tool for the evaluation of cutaneous lesions was previously demonstrated by Novelli et al, 14 who showed the presence of immunophenotypically aberrant T cells on skin punch biopsy specimens from 22 patients with various primary cutaneous T-cell malignancies, including 11 patients with MF. Similarly, Wu et al 13 showed the utility of FC in the diagnosis of cutaneous B-lymphoid proliferations in skin punch biopsy specimens.…”
Section: Discussionmentioning
confidence: 86%
“…Tissue suspensions were performed using an automated mechanical disaggregation device (Medimachine, Consul TS, Italy, distributed by Becton-Dickinson and Dakopatts, Denmark), as follows [33]: (1) small pieces of tissue, pretreated with 1% collagenase IA (Sigma, St. Louis, Mich., USA) were placed in microblade-equipped polyethylene chambers (Medicons, Consul TS) with 0.5–1.5 ml of suspension buffer (RPMI supplemented with 10% fetal calf serum and antibiotics) and inserted into the Medimachine; (2) fragments were dissociated for 20 s, at a constant speed of about 100 rpm; (3) recovered suspension buffer was filtered on porous polyester membranes (Filcons, Consul TS) with an effective surface area of 80 mm 2 . The cells were buffer washed after filtration and then processed for flow cytometry.…”
Section: Methodsmentioning
confidence: 99%